2015
DOI: 10.1111/padm.12118
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Healthcare Governance for Improvement? Combining Top‐down and Bottom‐up Approaches to Public Sector Regulation

Abstract: Improving healthcare governance is an enduring challenge for policy-makers. We consider two national healthcare regulators adopting novel 'hybrid' regulatory control strategies in pursuit of improvement. Hybrids combine elements usually found separately. Scotland's and Ireland's regulators combine: (1) top-down formal regulatory mechanisms deterring breaches of protocol and enacting penalties where they occur (e.g. standard-setting, monitoring, accountability); and (2) bottom-up capacity building and persuasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…These insights contribute to scholarship on network accountability, which has often focused on the decreasing importance of regulators in governance networks and the regulatory failures resulting from accountability conflicts in networks (Osborne ). Thus, this study concurs with recent case studies of other successful regulatory action in networks (McDermott et al ; Mills et al ; Reynaers and Parrado ) to contribute to our understanding of how regulators can act as change agents in networks, especially in settings with heterogeneous, conflicting perspectives and motives of network participants.…”
Section: Introductionsupporting
confidence: 89%
“…These insights contribute to scholarship on network accountability, which has often focused on the decreasing importance of regulators in governance networks and the regulatory failures resulting from accountability conflicts in networks (Osborne ). Thus, this study concurs with recent case studies of other successful regulatory action in networks (McDermott et al ; Mills et al ; Reynaers and Parrado ) to contribute to our understanding of how regulators can act as change agents in networks, especially in settings with heterogeneous, conflicting perspectives and motives of network participants.…”
Section: Introductionsupporting
confidence: 89%
“…); higher education reforms in Sweden, the UK, and the Netherlands (Teelken ); and reforms in Scotland and Ireland (McDermott et al. ). A second group concerns public–private relationships.…”
Section: An Outline Of the Articlesmentioning
confidence: 99%
“…This article focuses on structural hybridity; while identity and role hybridity are also studied elsewhere, for example within the welfare and health sector (cf. Denis et al ; Fossestøl et al ; McDermott et al ). The growing literature on collaborative public management has tended to treat networks as distinct from hierarchies, but recent research has shown that when actors organize to reach policy goals in practice, traces from both organizing principles are present (McGuire ; McDermott et al ).…”
Section: Designing Collaborative Disaster Management: Hierarchy Netwmentioning
confidence: 99%